Cathode material investigation towards high-performance aluminum batteries - Gong, Xuefei (Nanyang Technological University, 2020)
Aluminum (Al) batteries, with merits of cost effectiveness, safe handle, high capacity and dendrite-free formation of Al anode and utilization of non-flammable ionic liquid electrolyte, has been considered as promising alternative to lithium ion batteries. However, Al batteries suffer from sluggish kinetics of ion intercalation/de-intercalation and inferior cycling performance. It is due to the large electrostatic interactions between trivalent Al3+ and the framework of cathode materials, thus resulting in the destruction of the lattices of cathode materials, trapping Al3+ ions into the framework of cathode materials and hindering the subsequent Al3+ intercalation.